Organizational Culture as a Prerequisite for Knowledge Transfer among IT Professionals: The Case of Energy Companies - Anna Pietruszka-Ortyl; Małgorzata Ćwiek; Bernard Ziębicki; Anna Wójcik-Karpacz (Energies, 2021)
The energy sector is the epitome of Industry 4.0; therefore, it should be developed in line with the Industry 4.0 implementation framework and be managed according to the guidelines dedicated to knowledge-based enterprises. Under this model of evolution, the layers surrounding the technological aspects are first, knowledge management (in particular, its transfer), and then people, and culture. This study addresses two of the three identified levels by attempting to verify the organizational culture that supports professional knowledge transfer as the leading factor in effective specialist knowledge exchange in the energy sector. Recently, this sector has become highly dependent on IT solutions as the main factor for its development and security. A key role in this respect is played by IT professionals, whose attitudes and employee behavior are critical to the stability, efficiency, effectiveness, and security of IT systems in the energy companies. The purpose of this paper is to propose a theoretical construct, based on indicated norms and values as organizational culture foundation and cultural practices. This article also aims to analyze and diagnose the components that support the professional knowledge transfer in different groups of organizational stakeholders. Systematic analysis of the scientific literature, expert evaluation, and structured questionnaires were used to develop and verify the hypotheses. The research results supported the hypotheses that organizational culture tailored to the knowledge workers’ needs and expectations, influence the effective and efficient circulation of IT expert knowledge.